Change Business Model of Islamic Religious College Business in East Java by Building Integrated Online Policy and Technology Systems During the Covid-19 Pandemic Period - m.said, Ilham; Heri Cahyo Bagus Setiawan; Nuzulul Fatimah; Tatag Herbayu L (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2020)
This study conducted an analysis and evaluation of business services activities P erguruan T Heigh under the Ministry of Religious Affairs in J awa T imur to create a model of an integrated online system to maximize kan activities of the service business during a pandemic covid 19. Enterprises college business has expanded rapid and during the pandemic covid has made changes to the service online, after the application of social distance in an effort to deal with the spread of the disease corona virus (Covid-19). Initially, an increase in people's interest to shop online was to buy necessities of life very high with many transaction processes. The aim is to provide effective and efficient services to all business transactions conducted online during the pandemic covid19. The methodology used is a qualitative research method with case studies and using purposive samples . The analytical approach used is interpretive analysis. The results of the research show that implementing an integrated online system is able to serve many business transaction processing activities which are greatly improved. So it can be concluded several things as follows: With an integrated online system through planning and organizing business systems can illustrate the various classifications of implementation of business services online business activities in order to facilitate all forms of business transaction processes quickly, effectively and efficiently during Covid-19. System integration of online ie business opportunities using technology that can deliver greater value for the business of the college that the college of business can be developed and can be maintained as well as helping people to meet their needs and facilitate online transactions.